1-Methylcyclopropene maintains postharvest quality in Norwegian apple fruit. (July 2020) - Falagán, N; Terry, LA
Norwegian fruit production is mostly destined for the local market and can suffer from poor-quality retention during storage. 1-Methylcyclopropene (1-MCP) is an inhibitor of ethylene perception used to maintain the physical and functional quality of pome fruit. Extensive work has been carried out on the effect of 1-MCP on apples, but not on cultivars grown in Norway. In this work, the potential of 1-MCP application (0.625 ml l −1 for 24 h at 0 ± 1℃) for ripening control of the apple cultivars 'Aroma', 'Red Gravenstein', and 'Summered' was studied during 1 and 1.5 months of cold storage; both scenarios were followed by five days of shelf life. The application of 1-MCP reduced softening by an average of 12% in 'Aroma', 'Red Gravenstein', and 'Summered' apples when cold stored for both 1 and 1.5 months as compared to control. External colour remained similar to initial values in 1-MCP fruit when compared to control apples, which presented a significant skin darkening. This indicated a delay in the ripening process. 1-MCP treatment did not affect total soluble solids content. 'Aroma' samples treated with 1-MCP showed a low sucrose hydrolysis, indicating a slower ripening process. This work confirms that 1-MCP postharvest treatment shows great potential for maintenance of apple cvs. in Norway during cold storage and shelf life.